2014
DOI: 10.1021/nn5053734
|View full text |Cite
|
Sign up to set email alerts
|

Stacking in Colloidal Nanoplatelets: Tuning Excitonic Properties

Abstract: Cataloged from PDF version of article.Colloidal semiconductor quantum wells, also commonly known as nanoplatelets (NPLs), have arisen among the most promising materials for light generation and harvesting applications. Recently, NPLs have been found to assemble in stacks. However, their emerging characteristics essential to these applications have not been previously controlled or understood. In this report, we systematically investigate and present excitonic properties of controlled column-like NPL assemblies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
290
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 153 publications
(304 citation statements)
references
References 54 publications
13
290
1
Order By: Relevance
“…Thanks to their strong quantum confinement solely in the vertical direction, 2D CQWs possess many unique thickness‐dependent optical characteristics including ultranarrow emission with suppressed inhomogeneous broadening, giant oscillator strengths, extraordinarily large linear and nonlinear absorption cross‐sections, and molar extinction coefficients . All these superior properties render CQWs to offer great potential for optoelectronic applications including solar energy harvesting, lasing, and light‐emitting diodes (LEDs) …”
Section: Summary Of Led Performancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to their strong quantum confinement solely in the vertical direction, 2D CQWs possess many unique thickness‐dependent optical characteristics including ultranarrow emission with suppressed inhomogeneous broadening, giant oscillator strengths, extraordinarily large linear and nonlinear absorption cross‐sections, and molar extinction coefficients . All these superior properties render CQWs to offer great potential for optoelectronic applications including solar energy harvesting, lasing, and light‐emitting diodes (LEDs) …”
Section: Summary Of Led Performancesmentioning
confidence: 99%
“…Therefore, it is reasonable that low AR based CQW‐LEDs exhibits the highest EQE among these three devices. On the other hand, the stacking in CQW films is detrimental to the efficiency through fast nonradiative exciton transfer giving defected sub‐populations, which act as exciton sinks, undermining the efficiency of LEDs . As HAADF TEM images clearly show in Figure S6 (Supporting Information), negligible stacking is observed in low AR CQWs while stacking exists in high AR CQWs, suppressing the efficiency reduction in low AR devices .…”
Section: Summary Of Led Performancesmentioning
confidence: 99%
“…For these stacked NPLs, strongly quenched photoluminescence has been reported arising from ultraeffi cient exciton transport assisted hole trapping. [ 13 ] Up to now, to enhance stability and PL-QY of NPLs, core/ crown (laterally grown shell) [14][15][16][17][18] and core@shell (vertically grown shell) [ 19,20 ] architectures have been synthesized and studied intensively. Among different varieties of core/crown (C/C) NPLs, CdSe/CdS C/C NPLs have been one of the most widely studied material systems.…”
Section: Introductionmentioning
confidence: 99%
“…Addition of an antisolvent such as ethanol accelerates the stacking drastically. This provides a way to control the stacking by purposefully adding small amounts of antisolvent to a stable dispersion …”
Section: Self‐assembly Of Nanoplateletsmentioning
confidence: 99%
“…This phenomenon has recently been shown to be the origin of the decrease in quantum yield of stacked NPLs. Upon addition of an antisolvent, Guzelturk et al . evidenced this loss of fluorescence and showed that it was coupled to a significant acceleration of the transient fluorescence decay.…”
Section: Effect Of Self‐assembly On Optical Propertiesmentioning
confidence: 99%